Textbook representation of prepositions - Mukundan, Jayakaran; Roslim, Norwati (2009)
This article presents a corpus-based investigation on English prepositions which are presented in three English language textbooks used by lower secondary schools in Malaysia. The aims were to find out the distributions of prepositions, its frequency order in comparison with the British National Corpus (BNC) and the differences in terms of their co-occurrence with other parts of speech. The findings showed that there is a difference between the textbook corpus and the BNC in terms of the frequency order of certain prepositions and there are similarities and differences in terms of their co-occurrence with other parts of speech. This study indicates the textbook corpus is essential in the study of prepositions and the results can guide teachers in deciding how best to supplement the text with activities that will give learners exposure to target grammar item that is not sufficiently presented in the textbook.